1995
DOI: 10.1002/jlb.58.6.675
|View full text |Cite
|
Sign up to set email alerts
|

An analogue of lipid A and LPS from Rhodobacter sphaeroides inhibits neutrophil responses to LPS by blocking receptor recognition of LPS and by depleting LPS-binding protein in plasma

Abstract: When incubated with lipopolysaccharide (LPS) in the presence of plasma, neutrophils become primed for enhanced release of superoxide in response to triggering by formyl-Met-Leu-Phe (fMLP). The effect of LPS on phagocytes is inhibited by a synthetic lipid A precursor, LA-14-PP (lipid IVa) or by LPS from Rhodobacter sphaeroides (Rs). We studied the mechanisms by which LA-14-PP or Rs-LPS inhibited LPS-induced responses. When neutrophils were exposed to LA-14-PP or Rs-LPS for 3 min and then to Escherichia coli-LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Probably the most often cited example is augmentation of superoxide production elicited by phorbol esters or fMLP [150][151][152][153]. Exposure of human PMNs to LPS causes the membrane localization of cytochrome b 558 , a subunit of the superoxide-generating enzyme, NADPHoxidase [154].…”
Section: Pmn Primingmentioning
confidence: 99%
“…Probably the most often cited example is augmentation of superoxide production elicited by phorbol esters or fMLP [150][151][152][153]. Exposure of human PMNs to LPS causes the membrane localization of cytochrome b 558 , a subunit of the superoxide-generating enzyme, NADPHoxidase [154].…”
Section: Pmn Primingmentioning
confidence: 99%
“…Although neutrophils responded to LPS in immobilized form and in solution with similar sensitivity, the requirement for cofactor was different, comparing the various forms of immobilized LPS and LPS in solution. Treatment of immobilized LPS in the form of LPS/plasma with anti-LBP antibody caused inhibition of priming, as has been shown with priming by LPS in solution [24]. But the antibody did not affect priming by immobilized LPS in other forms, namely plasma/LPS, fibrinogen/ LPS, and LPS/fibrinogen.…”
Section: Discussionmentioning
confidence: 55%
“…We showed that immobilized LPS acted on neutrophils, causing priming for enhanced release of O 2 Ϫ in response to fMLP, up-regulation of CD11b/CD18 and latent alkaline phosphatase, and enhanced adherence, all of which have been observed with LPS in solution [17,24]. The immobilized LPS was estimated to be 20% of the LPS used for coating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations